Going viral. Part II : the mindbending Minecraft graphic novel adventure! - Zoellner, David (Mortimer, 2021)
Minecraft avatar Steve and his human gamer Arby combine their skills to stop a virus from invading their Minecraft world. The pair must venture into the Nether to secure control of The Command Block before monsters get there first.